Efektifitas Pendekatan Konseling Behavioral pada Perilaku Self Harm di MANU Putri Buntet Pesantren - Azizah, Nur; Yasin, Ahmad Alamuddin (Journal of Islamic Education Counseling, 2022)
Adolescence will experience many physical and mental changes to reach adulthood. At this time, adolescents are in the process of finding their identity. So sometimes problems arise. From the various problems that occur, adolescents experience a decline both in terms of physical, psychological and social. One of the effects of these problems can make teenagers stress, depression and other bad things. As a result, the teenager may vent bad feelings, one of which is self-harm or self-harm. In this case the researcher conducts group counseling with a behavioral counseling approach that focuses on changing behavior to eliminate the self-harm behavior. Researchers used qualitative methods through interviews, observations and literature studies. The result of this research is the behavioral counseling process is proven to be effective in preventing self harm behavior in students.